ISLAMIC RADICALISM AND DE-RADICALIZATION STRATEGIES: A CONTRIBUTION OF NURCHOLISH MADJID - Ngainun Naim; As'aril Muhajir (Islam Futura, 2020)
This paper examines the phenomenon of Islamic radicalism and the contribution of Nurcholish Madjid in the context of de-radicalization. Islamic radicalism has rapidly developed a few years ago. This phenomenon has conduced widespread public anxiety. Various de-radicalization efforts have been carried out, but have not shown results as expected. In this framework, the offer of a de-radicalization strategy is important to be implemented. Nurcholish Madjid has a serious attention to the issue of both Islamic radicalism and de-radicalization. In case radical Islamic communities are not given adequate attention, the future of Indonesia as a pluralistic nation is threatened because it does not provide a conducive sphere for the development of various kinds of diversity.